Legal Efforts for Owners to Regain Their Certificates Related to the Criminal Case of Embezzlement of Land Certificates by Notaries - Sonia Claudia Candra; Abdul Madjid; Dyah Widhiawati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
In Indonesia, every land right, management right, waqf land and ownership right to a condominium unit are registered by recording them in a land book, which contains physical data and legal data of the land area in question and as long as there is a measurement letter, which is also recorded in the measurement letter. Normative research method. Civil Code (KUHPerdata) Article 1866 KUHPerdata: States that the legal owner of a land right has the right to prove his ownership. In cases of embezzlement, the owner can use legal proof of ownership to file a claim. Article 197: Regulates the restoration of lost rights, which can be used as a basis for filing an application for restoration of rights to embezzled certificates. Law No. 5 of 1960 concerning Basic Agrarian Principles (UUPA): Article 1 Paragraph (1), Article 37, Article 672. Government Regulation No. 24 of 1997 concerning Land Registration: Article 1 Paragraph (1). PP NO. 18 OF 2021: a series of activities carried out by the Government continuously, continuously and regularly including the collection, processing, bookkeeping and presentation as well as maintenance of physical and legal data from each plot of land owned by the community, legal entities and government agencies. In its implementation, the definition above is carried out based on the principles of simplicity, safety, affordability, up-to-date and openness. Basically, the issuance and cancellation of land title certificates can be done in two ways, namely cancellation due to a court decision and cancellation carried out by the BPN itself. because the court decision only assesses the validity / does not have legal force, while the cancellation of the certificate is the authority of the BPN, are two different things.